Examining the Hadith on the Effect of Division of Turns by Polygamous Husbands to Wives on Marital Satisfaction - Nurdin, Nurdin; Salma, Siti (PT. Sharia Journal and Education Center, 2024)
Abstract Polygamy, even though it is legal in Islamic teachings, often creates complexities, one of which is injustice towards wives. The unequal distribution of income, love and attention is a problem that arises. Injustice, especially in the distribution of shifts, can produce feelings of dissatisfaction on the part of the wife, where the lack of attention and affection from the husband is the main factor. Hadiths related to polygamy provide guidance regarding the importance of justice in distributing turns in order to create harmony in the household for husbands who practice polygamy. This research, using qualitative methods with a literature study approach, highlights the relevance of fair distribution of turns as a key element in maintaining household harmony in polygamy. The research results show that fairness in the distribution of turns is an important factor in maintaining balance and harmony in polygamy. Polygamy hadiths provide concrete instructions on how polygamous husbands can distribute their turns fairly to their wives. Fair distribution of shifts, defined as a distribution that does not burden certain parties, both in terms of quantity and quality, is an important key. In quantity, this includes giving equal turns in time and frequency to each wife. Meanwhile, in terms of quality, a fair distribution of turns includes equal attention, affection and fulfillment of needs for each wife. Fairness in the distribution of turns is a real form of justice that must be carefully maintained in the context of polygamy. The importance of justice is not only related to the wife's individual satisfaction, but also helps create broader harmony in a polygamous household. Keywords: marital satisfaction, husband's turn distribution, hadisth Abstrak Poligami, meskipun sah dalam ajaran Islam, kerap menimbulkan kompleksitas, salah satunya ialah ketidakadilan terhadap istri. Tidak meratanya pembagian nafkah, kasih sayang, dan perhatian menjadi permasalahan yang muncul. Ketidakadilan, terutama dalam pembagian giliran, dapat menghasilkan perasaan tidak puas pada pihak istri, di mana kurangnya perhatian dan kasih sayang dari suami menjadi faktor utama. Hadist-hadist terkait poligami memberikan pedoman mengenai pentingnya keadilan dalam pembagian giliran guna menciptakan keharmonisan dalam rumah tangga bagi suami yang mempraktikkan poligami. Penelitian ini, menggunakan metode kualitatif dengan pendekatan studi literatur, menyoroti relevansi pembagian giliran yang adil sebagai elemen kunci dalam memelihara harmoni rumah tangga pada poligami. Hasil penelitian menunjukkan bahwa keadilan dalam pembagian giliran adalah faktor penting dalam menjaga keseimbangan dan keharmonisan dalam poligami. Hadist-hadist poligami memberikan petunjuk konkret tentang bagaimana suami berpoligami dapat menjalankan pembagian giliran dengan adil untuk istri-istrinya. Pembagian giliran yang adil, didefinisikan sebagai pembagian yang tidak memberatkan pihak tertentu, baik dalam segi kuantitas maupun kualitas, menjadi kunci penting. Secara kuantitas, hal ini mencakup pemberian giliran yang setara dalam jumlah waktu dan frekuensi bagi setiap istri. Sementara itu, secara kualitas, pembagian giliran yang adil mencakup perhatian, kasih sayang, dan pemenuhan kebutuhan yang setara untuk setiap istri. Keadilan dalam pembagian giliran merupakan bentuk nyata dari keadilan yang harus dijaga dengan cermat dalam konteks poligami. Pentingnya keadilan ini tidak hanya berkaitan dengan kepuasan individual istri, tetapi juga membantu menciptakan keharmonisan yang lebih luas dalam rumah tangga poligami. Kata Kunci: kepuasan perkawinan, pembagian giliran suami, hadist